Prevalence and macro- and microscopic lesions produced by Gasterophilus nasalis (Diptera : Oestridae) in the Botucatu Region, SP, Brazil - Sequeira, J. L.; Tostes, R. A.; Oliveira-Sequeira, TCG (Elsevier B.V., 2001)
The objective of the present study was to investigate the prevalence of Gasterophilus nasalis larvae in Botucatu, the central west region of São Paulo State, Brazil, and to describe the lesions caused by the parasite. The climate of Botucatu is warm and rainy during the months of December through March and cool and dry during the months of May through August. The prevalence of G. nasalis was 16.84%, and the period of peak infestation corresponded to the months of cold and dry weather. The lesions detected at the sites of larval attachment were examined macro- and microscopically. Erosions and ulcerations of the gastric mucosa and proximal duodenum were the major macroscopic lesions detected. Microscopically, the lesion spectrum ranged from mild inflammatory reactions to extensive necrosis and ulceration. (C) 2001 Elsevier B.V. B.V. All rights reserved.
Keywords: Gasterophilus nasalis; prevalence; lesions; horse; Brazil